OPTIMIZATION OF CARAGENAN CONCENTRATION IN THE PRODUCTION OF NORI IPOMOEA REPTANS SNACKS BASED ON ORGANOLEPTIC TESTING - Anggi Anggraeni; Cartono; Mia Nurkanti (PT. Jurnal Center Indonesia Publisher, 2025)
Nori is a seaweed-based food that is favored by the Indonesian people, but its availability is still limited. Meanwhile, the abundant production of land kale (Ipomoea reptans) as a local vegetable has not been optimally utilized, resulting in low economic value and its potential as a food source has not been maximized. One solution to overcome this problem is to use organic land kale as an alternative ingredient for making nori. Organic land kale is known to have good nutritional content and is commonly consumed by the community. This study aims to determine the level of acceptance of analog nori made from organic land kale as a healthy snack through organoleptic tests. The method used was an experiment with a completely randomized design (CRD), consisting of 24 samples, 6 treatments, and 4 repetitions. The treatment given was carrageenan concentration (0%, 0.6%, 0.8%, 1%, 1.2%, and 1.4%) Data were analyzed using the Friedman Test to assess panelists' preferences for taste, color, aroma, and texture parameters. It can be concluded that the results show the addition of carrageenan at 1% produces analog nori with the highest level of acceptance, so it is considered the most optimal formulation.